Shifting Patterns of Ocular Emergencies: A Comparative Study in Basrah, Iraq - Mokhles Jerri Meften Al-Sabti; Khalid Tawfeeq Najm Alsayab (Sriwijaya Journal of Ophthalmology, 2024)
Introduction: Ocular emergencies present a significant public health concern, potentially leading to vision loss if not addressed promptly. Understanding the dynamics of these emergencies is essential for effective healthcare planning and resource allocation. This study aimed to analyze the trends and characteristics of ocular emergencies in Basrah, Iraq, and compare them with historical data. Methods: A retrospective study was conducted at Al-Sayab Teaching Hospital in Basrah, involving 250 patients presenting to the ophthalmology emergency department between January 1st, 2023, and December 31st, 2023. Data regarding demographics, presentation time, causes of emergencies, and visual acuity were analyzed. Results: The leading causes of ocular emergencies were inflammatory diseases (32%), trauma (28%), and foreign bodies (33.2%). A significant proportion of patients (20%) presented with severe visual impairment (less than 20/200). Most emergencies occurred in males (72.4%), primarily in the 20-40 year age group. Conclusion: The study highlights a high prevalence of inflammatory diseases and trauma among ocular emergencies in Basrah. Public health interventions should focus on preventing ocular trauma and improving access to eye care services. Continuous monitoring of these patterns is crucial for effective public health planning.